Testosterone Delays Bone Microstructural Destruction via Osteoblast‐Androgen Receptor‐Mediated Upregulation of Tenascin‐C - Yong Xie; Meng Pan; Zeyuan Zhang; Licheng Zhang; Haotian Liu; Xia Wang; William W Lu; Peifu Tang; Wei Ge (Advanced Science)
Abstract Bone loss and microstructural destruction in elderly men are associated with fractures and high mortality. While testosterone (Tes) is considered to be possibly protective, its regulatory mechanism in bone remodeling remains unclear. Here, bone microarchitectural analysis indicates that elderly men exhibit reduced cortical and trabecular thickness with elevated cortical porosity, particularly at the superior femoral head near the medial acetabulum. Serum profiling of 352 individuals showed that low Tes levels (<9.415 nmol·L−1) are associated with higher risk of bone loss. In vivo, tail‐suspended mice lacking osteoblastic androgen receptor (AR) displayed similar femoral deterioration, with decreased trabecular bone and increased cortical porosity. Mechanistically, Tes enhances osteoblastic differentiation via AR‐mediated upregulation of tenascin‐C (TNC). Molecular docking suggests the fibrinogen C‐terminal domain of TNC inhibits osteoclastogenesis by binding integrin αV, blocking adhesion of RGD‐containing proteins. A synthetic peptide (pep2) mimicking this domain preserved bone architecture in osteoblast‐specific Ar‐knockout, tail‐suspended mice. Moreover, elevated serum extracellular vesicle amyloid precursor protein, secondary to Tes‐AR‐TNC decline and osteoclast overactivation, emerged as a biomarker of bone loss when combined with low Tes. This study identifies the Tes‐AR‐TNC axis as a key regulator of male bone remodeling, offering insights into fracture risk assessment and targeted interventions in bone destruction.